Bankruptcy because the Honor of the Management has not been agreed between the Management and the Debtor in PKPU (Case Study of the Commercial Court Decision at the Surabaya District Court Number 13 / PDT. SUS-PKPU/2023/PN NIAGA SBY) - Giysmar, Najib A; Dewi, Elya Kusuma (Greenation International Journal of Law and Social Sciences, 2024)
COVID-19 has had a significant impact on business actors in fulfilling their obligations to their business partners, so many business actors have requested the postponement of debt payment obligations (PKPU), including PT Mas Murni Indonesia Tbk (In PKPU). The Peace Agreement that was agreed upon between PT Mas Murni Indonesia (In PKPU) and 100% of its Creditors was rejected by the supervisory judge and the Panel of Judges, considering that there was no agreement between the Management Team and PT Mas Murni Indonesia (In PKPU).